226k views
2 votes
If f(x)=−x^2−8x+7, and g(x)=x−1, what does (g−f)(x) equal?

(g−f)(x)=−x^2−7x+6
(g−f)(x)=x^2+9x−8
(g−f)(x)=−x^2−9x+8
(g−f)(x)=−8x+8

User Jolmos
by
5.6k points

1 Answer

4 votes

Answer:

(g-f)(x) = x^2 + 9x - 8

Explanation:

To find the expression (g-f)(x) subtract the two expressions from each other by distributing a negative into the f(x) and combining like terms.

(g-f)(x) = x-1 -(-x^2 - 8x + 7)

(g-f)(x) = x - 1 + x^2 + 8x -7

(g-f)(x) = x^2 + 9x - 8

User Ron Cohen
by
6.2k points